2018
DOI: 10.1016/j.intfin.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Common information in carry trade risk factors

Abstract: Carry returns have been widely observed in the FX market. This study exploits the common information embedded in several factors previously identified as relevant to carry trade returns. We find that the extracted common factor successfully models the time series and cross-sectional characteristics of carry returns. Empirical evidence is presented that the common factor produces smaller pricing errors than other well known factors, such as innovations of exchange rate volatility and the downside stock market e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
2
5
0
1
Order By: Relevance
“…This is consistent with the findings of Burnside et al (2011) and Menkhoff et al (2012), where carry-trade portfolio returns appear to be unrelated to traditional risk factors. It also supports the conclusion drawn by Byrne et al (2018) that, based on the larger pricing error of stock market downside risk as compared to a common (carry trade) risk factor, currency and stock markets are not completely integrated, which will be quantified in the next two sections.…”
Section: Carry Trade Returnssupporting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with the findings of Burnside et al (2011) and Menkhoff et al (2012), where carry-trade portfolio returns appear to be unrelated to traditional risk factors. It also supports the conclusion drawn by Byrne et al (2018) that, based on the larger pricing error of stock market downside risk as compared to a common (carry trade) risk factor, currency and stock markets are not completely integrated, which will be quantified in the next two sections.…”
Section: Carry Trade Returnssupporting
confidence: 81%
“…Dobrynskaya (2014) and Lettau et al (2014) explained the cross section of carry-trade returns with an asset pricing model accounting for stock market downside risk. In contrast, Byrne et al (2018) showed that a common (carry-trade) risk factor produces smaller pricing errors compared to foreign exchange volatility and stock market downside risk. They concluded that carry trade portfolios are exposed to risk characteristics not captured by stock market downside risk and, thus, currency and stock markets are not completely integrated.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Characteristics related to different aspects of carry traders' activities in the foreign exchange market have been considered in many studies [48][49][50]. Based on investment styles, including carry trade, it is shown that carry trade is one of the most important factors that can explain most of the index of returns on professionally managed currency funds [51,52].…”
Section: Heterogeneous Agentsmentioning
confidence: 99%